Guidance note: Setting gender responsive sustainability standards - Petkova, Liliana; North, Hanna; Morgan, Miranda; Radford, Eleanor (2024)
Tackling gender inequalities is becoming increasingly important for voluntary sustainability systems to address. More and more, sustainability systems are looking to integrate gender into their standards and the management of their organisations. Sustainability systems that are not gender-responsive can result in unnecessary health and safety risks for women and girls, and lead to unequal impacts and unintended consequences. This briefing note provides a collection of good practices to support sustainability systems, including ISEAL Community Members, to get started and progress on gender issues.